Стабилизация параметров дуги в процессе размерной обработки деталей злектрической дугой - Смирнова, Н. В.; Смирнов, В. В.; Смірнова, Н. В.; Смірнов, В. В. (Національний університет харчових технологій, 2012)
The arcing mode control in the dimensional machining arc process problem solution submitted. The problem is solved by determining the optimal parameters of the arc regime and maintaining the arc process stability using the signal processing current and arc voltage correlation method.
Keywords: Electric arc; Correlation coefficient; Extremum; Setting action; Controller